Development of LKPD Based on Contextual Teaching And Learning (CTL) to Increase Learning Motivation in Algebra Form Material for Class VII MTs Thawalib Tanjung Limau Students - Zahra Salsabila; Isra Nurmai Yenti; Elda Herlina; Nola Nari (Edusainstika, 2025)
The purpose of this study is to create a product that is CTL-based LKPD to increase students' learning motivation that is valid, practical and effective. This study uses the Research and Development research method with a 4-D model which has 3 stages, namely the define, design and develop stages. The results of this research show that LKPD the CTL-based design designed is valid, practical and effective. The results of the validity of the LKPD are as many as 83.33% with a very valid category. Meanwhile, the practicality results of the CTL-based LKPD obtained from the student questionnaire results were 78.82% in the practical category. Furthermore, the results of the effectiveness of the LKPD can be seen from increasing students' learning motivation by using it the N-Gain percentage is 0.47 in the medium┬ácategory.┬á